Examining the incidence, depth and severity of food insecurity among rural households in Nigeria - Jabo, M. S. M.; Ismail, Mohamed. Mansor; Shamsuddin, Mad. Nasir; Abdullah, Amin Mahir; Maikasuwa, A. M. (International Institute for Science, Technology & Education, 2014)
A nationally representative sample of 3380 rural households from General Household Survey-panel data that adopt the World Bank Living Standard Measurement Survey (LSMS) technique was used for this study. Based on 2120 kcal Food and Agricultural Organization (FAO) recommended per adult equivalent and USD 0.87 purchasing power parity (PPP), an annual food poverty threshold of (N50, 331.67) equivalent to USD 317.55 per annum was derived for Nigeria. This threshold is the cost for purchasing recommended daily food allowances (RDA) of an adult equivalent for healthy life in rural Nigeria estimated at N138. Despite the fact that agricultural sector employed over 70% of the country’s population overwhelmingly large segment of Nigerians especially farming families in rural areas are the most food insecure. The food security situation in Nigeria was examined using the Foster Greer and Thorbecke (FGT) class of decomposable food poverty measures that satisfy both monotonicity and transfer axioms. The food insecurity indices at national level was reported as (∝=0, 46.36, ∝=1, 0.43 and ∝=2, 1.11 for and ∝=0, 42.78, ∝=1, 0.348 and ∝=2, 7.45) for post-harvest seasons respectively. This implies that almost half of the rural households in Nigeria are food insecure subsisting on less the RDAs, however, depth and severity of food insecurity also differ. Disaggregating the households based geo-political zones and some key socio-economic characteristics, further indicates a significant differences based on the relative size of the coefficient of ∝. We conjecture that, the higher incidence of food security during post harvesting season might likely be due to inability of smallholder farmers to utilize their time into non-farm income generating activities due to high demand for labour for farm operations. The study recommends public policies that ensure provision of infrastructure such as roads and boosting farming among rural households.